2019
DOI: 10.1016/j.isci.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Regulates Olfactory Perceptual Learning through Effects on Adult Neurogenesis

Abstract: SummaryLearning to perceptually discriminate between chemical signals in the environment (olfactory perceptual learning [OPL]) is critical for survival. Multiple mechanisms have been implicated in OPL, including modulation of neurogenesis and manipulation of cholinergic activity. However, whether these represent distinct processes regulating OPL or if cholinergic effects on OPL depend upon neurogenesis has remained an unresolved question. Using a combination of pharmacological and optogenetic approaches, choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Other examples are neuropeptides like prolactin from the pituitary gland during pregnancy (Shingo et al 2003) or β-endorphin from hypothalamic neurons in hunger and satiety (Paul et al 2017). Taken together neuromodulatory changes in neurogenesis will be of great interest in the future, especially since a recent paper demonstrated that cholinergic effects on olfactory learning require adult neurogenesis (Schilit Nitenson et al 2019).…”
Section: Open Questions Concerning Neuromodulation In the Olfactory Bulbmentioning
confidence: 99%
“…Other examples are neuropeptides like prolactin from the pituitary gland during pregnancy (Shingo et al 2003) or β-endorphin from hypothalamic neurons in hunger and satiety (Paul et al 2017). Taken together neuromodulatory changes in neurogenesis will be of great interest in the future, especially since a recent paper demonstrated that cholinergic effects on olfactory learning require adult neurogenesis (Schilit Nitenson et al 2019).…”
Section: Open Questions Concerning Neuromodulation In the Olfactory Bulbmentioning
confidence: 99%
“…In this study, discrimination ability was assessed by distinguishing between similar odor pairs (mainly enantiomer substances), according to previous studies [ 17 , 18 ]. Animal experiments using rats and mice revealed that olfactory discrimination ability was increased by administration of physostigmine, an acetylcholine esterase inhibitor or by the optogenetic stimulation of basal forebrain cholinergic neurons projecting to the olfactory bulb [ 36 , 37 ]. During the discrimination task, basal forebrain cholinergic neurons are recruited [ 38 ] and extracellular acetylcholine releases in the neocortex and hippocampus are increased [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the process of neurogenesis and synaptogenesis, both the synthesis and the activity of neurotransmitters that can be involved in cellular signaling, differentiation, immune response, and cellular migration play an important role 21,22 . This model is applicable to the development of the visual system where, in addition to the role played by growth factors like the factor derived from the brain and the nervous growth factor, among others, neurotransmitters contribute to modulating the visual signal in the early ages of development 23 .…”
Section: Cholinergic Activity In the Visual Pathwaymentioning
confidence: 99%